Integration of models for low carbon economy - Belete, Getachew F. (2020)
Designing the transition to low carbon economy is a very complex task that touches upon a wide variety of climate-energy-economic systems. We need to explore the various possible climate mitigation scenarios at different temporal and spatial scales. However, due to the diversity of the involved disciplines it is difficult to find one complete and unified modeling approach that works equally well in all those different domains. As a result we have to select ‘appropriate’ models, which represent only specific aspects of the scenarios and assemble them ‘coherently’. In this research we have identified some challenges in integrating multidisciplinary models; and have developed a conceptual design for a multidisciplinary model integration framework that can harmonize the technical, semantic, and dataset aspects of interoperability.